Analisis Implementasi Pembelajaran Deep Learning pada Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Pung Amanda Nabel; Parlin Wahyuni (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2025)
Education plays a crucial role in shaping high-quality human resources capable of competing in the global era. It focuses not only on imparting knowledge but also on instilling moral values, character building, and developing critical thinking skills. However, in practice, many elementary school students still struggle with critical thinking—such as identifying problems, providing logical reasoning, drawing conclusions, and actively participating in discussions and problem-solving. One approach to addressing these issues is